Laboratory analysis of CSF among patients admitted in Neurosciences department in a tertiary care hospital - Sharma, Manisha; Jha, Beena; Chapagain, Manisha; Bhatt, Chandra Prakash; K.C., Bidur (Nepal Journal of Neuroscience, 2025)
Introduction: Cerebrospinal fluid evaluation is the single most important aspect of the laboratory diagnosis of meningitis. Analysis of the Cerebrospinal fluid abnormalities along with evaluation of biomarkers like Lactate dehydrogenase (LDH) and Adenosine deaminase (ADA) produced in bacterial, mycobacterial, and infections may greatly facilitate diagnosis and direct initial therapy. Methods: A prospective, descriptive cross-sectional study was done in a tertiary care hospital from 15th August-15th November, 2024 after obtaining ethical clearance. 65 patients who met the inclusion criteria and consented to participate were included in the study. Cerebrospinal fluid was collected aseptically and processed for biochemical analysis including estimation of LDH and ADA, cytology, Gram’s staining and culture using standard techniques. The data obtained were computed and analyzed using Statistical Package for Social Sciences 20.0 Version. Results: Total of 65 patients were enrolled and their Cerebrospinal fluid was analyzed, among which, 19 were diagnosed as bacterial meningitis, 7 as tubercular meningitis and 39 as viral meningitis. CSF ADA was 23.91±15.37 U/L (Mean±SD) in the tubercular meningitis group. p value of ADA was significant in tubercular meningitis when a cut off value of 10 U/L was taken. The mean LDH value in bacterial meningitis was 234.26±155.45 U/L (Mean±SD). p value of LDH in bacterial meningitis was significant. Conclusions: CSF biomarkers such as lactate dehydrogenase and adenosine deaminase are simple, rapid and effective diagnostic tools in differentiating the etiology of meningitis. Elevated CSF LDH levels are indicative of bacterial meningitis, whereas significantly increased CSF ADA levels are characteristic of tuberculous meningitis (TBM).